2018
DOI: 10.18632/oncotarget.23984
|View full text |Cite
|
Sign up to set email alerts
|

Neovascular PSMA expression is a common feature in malignant neoplasms of the thyroid

Abstract: AimPSMA (prostate-specific membrane antigen) is physiologically expressed in normal prostate tissue and over expressed in prostate cancer cells, therefore constituting a potential target for antibody-based radioligand therapy. Very recent imaging findings reported PSMA-PET/CT uptake in various thyroid lesions. We were therefore encouraged to systematically analyse PSMA expression in different benign and malignant thyroid lesions.MethodsImmunohistochemistry was used to detect PSMA expression in 101 thyroid lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 28 publications
2
44
2
3
Order By: Relevance
“…Lodewijk et al found PSMA positivity in neovasculature in more than 92% of medullary thyroid carcinoma, while the tumor cells were PSMA negative [22]. Heitkötter et al studied PSMA on IHC in PTC and follicular thyroid carcinoma and found positivity in tumor-associated neovasculature in 18 out of 31 and 4 out of 10 patients, respectively [23]. Moore et al investigated 37 patients and found PSMA significantly overexpressed in the neovasculature of DTC, particularly in RAI-refractory patients and in distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Lodewijk et al found PSMA positivity in neovasculature in more than 92% of medullary thyroid carcinoma, while the tumor cells were PSMA negative [22]. Heitkötter et al studied PSMA on IHC in PTC and follicular thyroid carcinoma and found positivity in tumor-associated neovasculature in 18 out of 31 and 4 out of 10 patients, respectively [23]. Moore et al investigated 37 patients and found PSMA significantly overexpressed in the neovasculature of DTC, particularly in RAI-refractory patients and in distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Silver et al showed no expression of PSMA in the thyroid gland [24]. A previous study has shown that neovascular PSMA expression is common in thyroid cancer but may also rarely be found in benign thyroid diseases, such as follicular adenoma [25]. (d) 68 Ga-PSMA-11 PET/CT can provide accurate localization and quantitative analysis for lacrimal glands.…”
Section: Discussionmentioning
confidence: 99%
“…Although the name implies specificity, PSMA expression is by no means exclusive to the prostate. There is physiologic high expression in the kidneys and small intestines and abnormal expression in a variety of benign and malignant nonprostatic processes, such as benign skeletal abnormalities (fractures, fibrous dysplasia) and other cancers (23,24). PSMA uptake in nonprostatic malignancies is related to PSMA expression of the tumor-related neovasculature (25).…”
Section: Pet/ctmentioning
confidence: 99%